Evaluation of Periodontal Health Adjacent to Class V Restoration - SUNIL, NURUL SYAMIMI BINTI MOHD AZLAN; RAJASEKAR, ARVINA; DURAISAMY, REVATHI (The journal of contemporary issues in business and government, 2021)
Periodontal health and dental restoration are inseparably interrelated. The margin adaptation, the proximal relationship, the contours of restoration and the smoothness of restoration surface have a major biological impact on the gingiva and supporting periodontal structures. Cervical placed restorative margins usually have a detrimental effect of periodontal health. The aim of the present study was to evaluate the periodontal health adjacent to class V restoration. The retrospective study was conducted using the case records of patients in a private dental institution between June 2019 to March 2020. A total of 942 patients (159 females and 783 males) with class V restorations were recruited. Data regarding the periodontal status of the patients were collected from their records. Descriptive and inferential statistics were done using SPSS software. The present study showed 95.1% of teeth demonstrated pocket depth of 1-3 mm and 4.9% had pocket depth of 4mm or more. 65.7% of teeth presented with clinical attachment loss and prevalence was more males (67%) compared to females (59.1%). 84.5% of teeth were observed to have bleeding on probing and prevalence was more in males (85.8%) compared to females (78%). Statistically significant association was found between clinical attachment loss and class V restoration and also between bleeding on probing and class V restoration. Within the limitation of this study, it can be concluded that most teeth with class V restoration presented with clinical attachment loss (65.7%) and bleeding on probing (84.5%). Also, males showed higher prevalence of clinical attachment loss and bleeding on probing when compared to females.